Effect of aged crumb rubber bitumen on performance dense graded mix in Malaysia - Al Qudah, A. (IAEME Publication, 2018)
To prevent pavement failure there are different solutions such as adopting new mix methods or utilization of waste materials as additives. The main objective of this study is to evaluate the effect of crumb rubber (CR) added to bitumen binder as a reinforcing material on dense graded asphalt (DGA) mixture performance. The performances of the DGA mixture were investigated by means of Marshall Stability and flow test, stiffness test, indirect tensile strength test and cantabro test on DGA samples before and after exposing unmodified and modified binders to aging process. In this study, bitumen PEN (60/70) was utilized, modified with CR at three various modification levels, namely, 5, 10, and 15, respectively, by weight of the asphalt binder. The optimum content of the added CR was found to be 5-10. This percentage results in the best level of stability and stiffness, maximum indirect tensile strength and lower flow. The modified samples at different of CR contents were obviously better properties in comparison with that of unmodified samples. It could be concluded that reinforcement of binders by CR is a successful and beneficial technique. Â© IAEME Publication.